COMMUNITY-BASED FACILITIES MANAGEMENT: THEORY AND PRACTICE - Rozilah Kasim (Penerbit UTHM, 2011)
This book introduces an alternative framework for the discipline of facilities management that challenges its existing conventional practice of delivering services for organisation settings and recommends new approaches for achieving optimum business performance as well as social and public interests. Experience from case study findings suggests that successful facilities managers need a range of skills and competencies that integrate professional skills and people-based skills that are more generic and soft. Its provides structured source of references that assist to consolidate and build on existing knowledge in both theories and practices, recognises that community-based skills are as an addition to the professional skills’ key requirement for organisational success. Its also emphasises the importance of integrating all stakeholders work together in new and innovative setting for sustaining quality service delivery within economic, social and environmental dimensions in support of social and public interests, and have overviews a community-based facilities management thinking and practice for housing neighbourhood facilities in Malaysia.